Budget visualizer using circle packing technique / Nursyahira Zulkeply - Zulkeply, Nursyahira (2019)
Data visualization is used to analyse the patterns and trends of data, including budget distributions, business analytics and so forth in a form of diagrams, charts and so on. In Malaysia, the budget is still in the form of a speech text and info graphics. In previous study, treemap visualization technique is used to visualize the Malaysia budget, but it has resulted to data congestion as there are too many ministries and its programs in Malaysia. Besides, the visualization failed to compare previous and current budgets. Therefore, this study uses circle packing technique to visualize the Malaysia’s budget where it provides a more presentable and interactive way to explore the budget that can compare the current and previous budget on a single website. In order to construct this data visualization, the circle packing algorithm is used to visualize these budgets. Json file is used to reorganise the budgets data and imported as input file. Circle packing algorithm includes creating a new pack layout, then packing the root node by assigning coordinate x, y and radius. Besides, it needs to pack the radius, then setting the size using two elements of array. It follows by setting the padding and packing the array of siblings circles. Lastly, it encloses the circles to the packing. This algorithm is then integrated with Json file and HTML to visualize it interactively on the web. This dynamic budget visualization webpage is a better option of exploration and it is beneficial to Malaysians as it helps the citizen in seeing a clearer picture of the distributions of their money. Furthermore, it is handy to understand the government future financial planning for Malaysia in an interactive way. This algorithm can be reusable to visualize any other financial data in hierarchy structure.